2010
DOI: 10.1097/yic.0b013e32833948fa
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of paliperidone palmitate in adult patients with acutely symptomatic schizophrenia: a randomized, double-blind, placebo-controlled, dose-response study

Abstract: This 13-week, double-blind study evaluated the efficacy and safety of the atypical antipsychotic paliperidone palmitate (recently approved in the United States) versus placebo administered as monthly gluteal injections (after two initial doses given 1 week apart) in acutely symptomatic patients with schizophrenia. Patients (N=388) were randomly assigned (1 : 1 : 1 : 1) to paliperidone palmitate 50, 100, or 150 mg eq. or placebo. As the 150 mg eq. dose was administered to fewer patients (n=30) than planned, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
118
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 19 publications
29
118
2
1
Order By: Relevance
“…These results are generally consistent with those from other recent studies of paliperidone palmitate for both the acute and maintenance treatment of patients with schizophrenia (Gopal et al, 2010;Hough et al, 2008Hough et al, , 2009Kramer et al, 2010), as well as for the oral formulation, paliperidone (Davidson et al, 2007;Kane et al, 2007;Kramer et al, 2007;Luthringer et al, 2007;Marder et al, 2007). Although in this study, paliperidone palmitate was administered gluteally, it may be administered in the deltoid muscle as well (Hough et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…These results are generally consistent with those from other recent studies of paliperidone palmitate for both the acute and maintenance treatment of patients with schizophrenia (Gopal et al, 2010;Hough et al, 2008Hough et al, , 2009Kramer et al, 2010), as well as for the oral formulation, paliperidone (Davidson et al, 2007;Kane et al, 2007;Kramer et al, 2007;Luthringer et al, 2007;Marder et al, 2007). Although in this study, paliperidone palmitate was administered gluteally, it may be administered in the deltoid muscle as well (Hough et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, discontinuation of oral APs for safety or tolerability as a first treatment failure event appeared to be similar for both groups (Table 3). Overall, the AE profile of PP was consistent with that reported previously; the most notable events were well‐established risks for injection site pain, akathisia, weight gain and elevated prolactin levels 37, 38, 39. Because individual oral APs included as potential comparators in this study could be deselected and because the documented reasons for deselection were usually related to a history of AEs, relative rates for these events were likely underrepresented in this study.…”
Section: Discussionsupporting
confidence: 79%
“…It appears that methodological factors may in part explain differences in placebo response [64,65]. However, placebo responses of a similar magnitude and pattern to those observed in the trials examined here have been demonstrated in similarly designed PP studies in comparable, ethnically diverse patient populations [66,67]. This lends support to the generalizability of the placebo effect observed in this study and to the conclusion drawn regarding the efficacy of PP relative to placebo.…”
Section: Placebo Responsesupporting
confidence: 66%